Muhammadiyah's Contribution to Educational Development in Indonesia: A Historical Analysis - Pahlevi, Rijal; Badrudin, Badrudin; Ulfiah, Ulfiah (Jurnal Iman dan Spiritualitas, 2024)
Muhammadiyah's role in the development of education in Indonesia continues to grow over time, playing a key role in determining the future of this country. This research aims to dig deeper into Muhammadiyah's contribution to the history of the development of Indonesian education using historical methods. Literature study is used as a data collection technique, taking information from various sources such as books, journals, newspapers, the internet, and other references related to Muhammadiyah. The research results show that Muhammadiyah has had a positive impact by spreading Islamic teachings and designing an equitable education system throughout Indonesia. Muhammadiyah schools, which integrate religious and general lessons, make a significant contribution to advancing education in the country. This organization has succeeded in establishing and managing more than 5,264 schools and madrasas, as well as 177 universities throughout Indonesia. Thus, Muhammadiyah not only educates the nation through education but also forms quality individuals in educational and religious aspects.